CircRNA Is a Rising Star in Researches of Ocular Diseases - Zhang, Chengshou; Hu, Jianghua; Yu, Yibo (Frontiers in Cell and Developmental Biology, 2020)
A newly re-discovered subclass of non-coding RNAs, circRNAs, is produced by a back-splicing mechanism with a covalently closed loop structure. They not only serve as the sponge for miRNAs and proteins but also regulate gene expression and epigenetic modification, translate into peptides, and generate pseudogenes. Dysregulation of circRNA expression has opened a new chapter in the etiology of various human disorders, including cancer and cardiovascular, neurodegenerative, and ocular diseases. Recent studies recognized the vital roles circRNAs play in the pathogenesis of various eye diseases, highlighting circRNAs as promising biomarkers for diagnosis, assessment of progression, and prognosis. Interventions targeting circRNAs provide insights for developing novel treatments for these ocular diseases. This review summarizes our current perception of the properties, biogenesis, and functions of circRNAs and the development of circRNA research related to ophthalmologic diseases, including diabetic retinopathy, age-related macular degeneration, retinopathy of prematurity, glaucoma, corneal neovascularization, cataract, pterygium, proliferative vitreoretinopathy, retinoblastoma, and ocular melanoma.